2013
DOI: 10.1242/dev.098301
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental evidence indicates that there is no detectable auxin gradient in the angiosperm female gametophyte

Abstract: The plant life cycle alternates between a diploid sporophytic and a haploid gametophytic generation. The female gametophyte (FG) of flowering plants is typically formed through three syncytial mitoses, followed by cellularisation that forms seven cells belonging to four cell types. The specification of cell fates in the FG has been suggested to depend on positional information provided by an intrinsic auxin concentration gradient. The goal of this study was to develop mathematical models that explain the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 57 publications
4
69
1
Order By: Relevance
“…In what is now a familiar theme, this gradient of cytokinin mirrors an auxin gradient present in the sporophytic tissue early in female gametophyte development (Pagnussat et al, 2009) that is likely formed through the action of PIN1 (Ceccato et al, 2013). This auxin gradient was suggested to define cell-type specification in the female gametophyte (Pagnussat et al, 2009), though Lituiev et al (2013) suggested, on theoretical grounds and an analysis of a degron-based auxin sensor, that there was no auxin gradient in the female gametophyte itself, though they did observe a gradient in the surrounding sporophytic tissue. This suggests that in the sporophytic tissues, there are opposing auxin and cytokinin gradients that play complementary roles during early stages of female gametophyte development, including the specification of the functional megaspore cell from the four products arising from meiosis of the megaspore mother cell (C.-Y.…”
Section: Gynoecium and Female Gametophyte Developmentmentioning
confidence: 94%
“…In what is now a familiar theme, this gradient of cytokinin mirrors an auxin gradient present in the sporophytic tissue early in female gametophyte development (Pagnussat et al, 2009) that is likely formed through the action of PIN1 (Ceccato et al, 2013). This auxin gradient was suggested to define cell-type specification in the female gametophyte (Pagnussat et al, 2009), though Lituiev et al (2013) suggested, on theoretical grounds and an analysis of a degron-based auxin sensor, that there was no auxin gradient in the female gametophyte itself, though they did observe a gradient in the surrounding sporophytic tissue. This suggests that in the sporophytic tissues, there are opposing auxin and cytokinin gradients that play complementary roles during early stages of female gametophyte development, including the specification of the functional megaspore cell from the four products arising from meiosis of the megaspore mother cell (C.-Y.…”
Section: Gynoecium and Female Gametophyte Developmentmentioning
confidence: 94%
“…Abolishing the auxin gradient, by expressing the YUCCA1 (YUC1) auxin biosynthetic protein in the entire embryo sac or by modulating the auxin response by downregulating selected AUXIN RESPONSE FACTOR (ARF genes), led to the loss or, at low frequencies, the mis-expression of cell fate markers in the female gametophyte (Table 3; Pagnussat et al, 2009). However, theoretical models attempting to describe the auxin gradient in the female gametophyte showed that only very shallow auxin gradients can be established even when using the most favourable parameters (Lituiev et al, 2013). A sensitivity analysis demonstrated that the steepness of the obtained gradients is not sufficient to determine distinct cell fates (Lituiev et al, 2013).…”
Section: The Role Of Auxin and Cytokinin In Establishing And Maintainmentioning
confidence: 99%
“…However, theoretical models attempting to describe the auxin gradient in the female gametophyte showed that only very shallow auxin gradients can be established even when using the most favourable parameters (Lituiev et al, 2013). A sensitivity analysis demonstrated that the steepness of the obtained gradients is not sufficient to determine distinct cell fates (Lituiev et al, 2013). Furthermore, the reinvestigation of auxin signalling using various sensors failed to detect auxin in the female gametophyte but instead found auxin signalling to be restricted to the surrounding ovule tissues in a dynamic polar pattern (Ceccato et al, 2013;Lituiev et al, 2013).…”
Section: The Role Of Auxin and Cytokinin In Establishing And Maintainmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellularization and differentiation of cells in the embryo sac appear to be transcriptionally regulated (Rabiger and Drews, 2013), and mechanisms involving RNA splicing and auxin and peptide signaling specify female gametic cells (Gross-Hardt et al, 2007;Pagnussat et al, 2009;Lieber et al, 2011;Lituiev et al, 2013). For male germline development, a regulatory framework for cell cycle progression and gamete specification has been established Borg and Twell, 2010;Twell, 2011).…”
Section: Introductionmentioning
confidence: 99%